Analisis Komponen Kimia pada Liquid Volatile Matter Kulit Biji Mete Menggunakan Metode Gas Chromatography - Muhammad Jahiding; Ita Kurniasih; W.S. Ilmawati (Jurnal Aplikasi Fisika, 2016)
The purpose of this study was to determine the effect of temperature pyrolysis to chemical component Liquid Volatile Matter (LVM) cashew nut shell. Cashew nut shell is dried, then pyrolysed in the reactor at the temperature of each 400oC, 500oC, 600oC, and 700°C. Pyrolysed cashew nut shell produces smoke condensed known as Liquid Volatile Matter. LVM volume of cashew nut shell is measured using a measuring cup and the building blocks of LVM characterized using Gas Chromatography (GC). At any temperature pyrolysis, the volume of cashew nut shell LVM is different, each 100 ml, 150 ml, 150 ml and 125 ml. Similarly, the type of compound and the percentage vary at any temperature pyrolysis. LVM cashew nut shell composed of ammonia, hydrazine, hexane, acetic acid, and phenol.